Intercropping of taro and sunn hemp with cutting periods during the cycle - João Nacir Colombo; Mário Puiatti; Jaime Barros da Silva Filho; Ricardo Henrique Silva Santos; Luiz Antônio dos Santos Dias (Revista Ceres)
ABSTRACT Intercropping using legumes is one of the ways to protect the main crop, and in long term improve the physical and chemical properties of the soil. The aim of this work was to evaluate the intercropping of Colocasia esculenta (L.) Schott (taro) and the tropical legume Crotalaria juncea L. (sunn hemp), cutting sunn hemp at ten periods during the cycle. The experiment was carried out under field conditions between 09/23/2010 and 06/04/2011. It consisted of 11 treatments related to the 10 cutting times of sunn hemp (55, 70, 85,100, 115, 130, 145, 160, 190, and 220 days after sowing - DAS) plus a control of taro with no sunn hemp. During the cycle, taro was evaluated for plant height and incidence of leaf burn. At the time of cutting the sunn hemp, the plant height, fresh and dry matter masses, and nutrient content of the biomass were calculated. During taro harvest, we evaluated the productivity of the mother rhizomes and classified the cormels. Taro plants shaded by sunn hemp showed a lower incidence of leaf burn. The sunn hemp cut from 145 DAS onwards affected the yield of comercial rhizomes and total and agroeconomic indexes. Sunn hemp cut up to 130 DAS provided better performance of taro, without compromising productivity and economic indicators, with the highest amounts of N and K observed in the biomass cut at 115 DAS.